Markers of cognitive function in individuals with metabolic disease: Morquio syndrome and tyrosinemia type III. Issue 3 (19th May 2018) - Blundell, James; Frisson, Steven; Chakrapani, Anupam; Kearney, Shauna; Vijay, Suresh; MacDonald, Anita; Gissen, Paul; Hendriksz, Chris; Olson, Andrew
ABSTRACT: We characterized cognitive function in two metabolic diseases. MPS–IVa (mucopolysaccharidosis IVa, Morquio) and tyrosinemia type III individuals were assessed using tasks of attention, language and oculomotor function. MPS–IVa individuals were slower in visual search, but the display size effects were normal, and slowing was not due to long reaction times (ruling out slow item processing or distraction). Maintaining gaze in an oculomotor task was difficult. Results implicated sustained attention and task initiation or response processing. Shifting attention, accumulating evidence and selecting targets were unaffected. Visual search was also slowed in tyrosinemia type III, and patterns in visual search and fixation tasks pointed to sustained attention impairments, although there were differences from MPS–IVa. Language was impaired in tyrosinemia type III but not MPS–IVa. Metabolic diseases produced selective cognitive effects. Our results, incorporating new methods for developmental data and model selection, illustrate how cognitive data can contribute to understanding function in biochemical brain systems.